3D stream and vortexes in the urban canopy layer and transport of motor vehicles exhaust gas. (1st September 2005) - Kono, Hitoshi; Kusunoki, Kimiyo
Wind-tunnel experiments were conducted to investigate the transport of motor vehicle exhaust gas in the vicinity of a street. The stream and the vertical and horizontal vortexes in 2D and 3D street canyons were visualised using smoke. They were recorded by video camera and the transport of the exhaust gas by vortexes was then investigated. The vertical vortex plays a significant role in the vertical exchange between in-canyon flow and outer flow, and transports the exhaust gas outside the street canyons. The horizontal vortexes transport air pollutants to the next intersecting street. The relationships between functions of the vortexes and several assumptions in the Osaka Municipal Government (OMG) volume-source model are discussed.